Proteomics study on the changes in amino acid metabolism during broccoli senescence induced by elevated O2 storage. (July 2022) - Zhang, Yuxiao; Chen, Ying; Guo, Yanyin; Ma, Yangli; Yang, Mei; Fu, Ruiqing; Sun, Yupeng
Graphical abstract: Highlights: Amino acid metabolism in broccoli was revealed by proteomics under high O2 stress. High O2 stress induced amino acid degradation to support the TCA cycle. High O2 stress disrupted the urea cycle, thereby aggravating ammonium toxicity. Amino acids, the precursors of glucosinolate, were reduced under high O2 stress. High O2 stress induced ethylene anabolism and methionine catabolism. Abstract: To better understand the global changes of amino acid catabolism and anabolism in broccoli in response to high O2 stress, iTRAQ-based proteomics combined with amino acid analysis was used to investigate the broccoli proteome at 0 and 4 d after treatment with different O2 concentrations (5% O2  + 5% CO2, 20% O2  + 5% CO2 and 40% O2  + 5% CO2 ) at 20℃. A total of 106 proteins with changes ≥ 1.2-fold in abundance were observed. Amino acid anabolism was significantly suppressed by high O2 stress, while catabolism was enhanced. High O2 stress-induced amino acid metabolism promoted the conversion of Met to ethylene and the degradation of amino acids to intermediate metabolites of the TCA cycle, thereby suppressing glucosinolate biosynthesis. However, the up-regulation of arginase and urease induced by high O2 stress aggravated ammonium toxicity. These findings enhance our understanding of high O2 stress-induced amino acid metabolism, as well as the effects of amino acid metabolism on broccoli senescence.